Efektivitas Media Booklet dalam Meningkatkan Pengetahuan tentang Gizi Seimbang dan Keragaman Pangan dalam Pencegahan KEK pada Remaja SMAN 1 Telukjambe, Karawang: The Effectiveness of Booklet Media in Increasing Knowledge of Balanced Nutrition and Food Diversity in the Prevention of CED in Adolescents at SMAN 1 Telukjambe, Karawang - Fairuz Fatin (JURNAL GIZI DAN KESEHATAN, 2023)
Adolescence is a period of transition from children to adults. Adequacy of nutrition in adolescence is very necessary for growth and development. If energy intake is unbalanced and lasts a long time, it can cause Chronic Energy Deficiency (CED). Nutrition counseling is given with the aim of increasing awareness of the adequacy of nutrients in adolescents. This study aims to determine the effectiveness of the booklet media used in nutrition counseling in class XII IPS 2 SMAN 1 Telukjambe, Karawang. This study uses a Pre-Experimental Design research with a one group pretest-posttest design model. The research subjects were 30 people. The data was then processed using the Wilcoxon test. The results of this study indicate that there is an increase in knowledge in class XII IPS 2 adolescents with a significance value of 0.001 (p-value <0.005). In conclusion booklet media is effectively used in nutrition education for adolescents.   ABSTRAK Masa remaja merupakan masa peralihan dari anak-anak menuju dewasa. Kecukupan gizi pada masa remaja sangat diperlukan untuk pertumbuhan dan perkembangannya. Apabila asupan energi tidak seimbang dan berlangsung lama, dapat menyebabkan terjadinya Kurang Energi Kronis (KEK). Penyuluhan gizi diberikan dengan maksud meningkatkan kesadaran akan kecukupan zat gizi pada remaja. Penelitian ini bertujuan untuk mengetahui efektivitas media booklet yang digunakan dalam penyuluhan gizi di kelas XII IPS 2 SMAN 1 Telukjambe, Karawang. Penelitian ini menggunakan desain penelitian Pre-Experimental Design dengan model one group pretest-posttest design. Subjek penelitian berjumlah 30 orang. Data kemudian diolah menggunakan uji Wilcoxon. Hasil dari penelitian ini menunjukkan terdapat peningkatan pengetahuan pada remaja kelas XII IPS 2 degan nilai signifikansi 0,001 (p-value<0,005). Kesimpulannya media booklet efektif digunakan dalam penyuluhan gizi pada remaja.